2019
DOI: 10.5005/jp-journals-10005-1678
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Microbiological Evaluation after Caries Removal by Various Burs

Abstract: Aim:The aim of the study was to compare the caries removal efficacy in terms of bacteriology and efficiency in terms of time taken by conventional and smart burs. Materials and methods: A total of 40 extracted permanent molars with occlusal caries were selected for this study. These teeth were split at the center of carious lesion buccolingually, in order to obtain two similar halves. Thus, 80 samples were obtained in this way and were randomly divided into 2 groups of 40 samples each. Caries was removed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…However, in this investigation, the longer diagonal of the Knoop was compensated by the difficulty in determining where the tapered tip finishes on the surface of the dentin. 31 Without taking into account changes in indentation loads and time, the results obtained in this investigation for the KHN and VHN values of enamel and dentin are consistent with previously reported values: for example, the hardness of enamel has been reported in the range of 314 to 361 KHN 32 or 322 to 353 VHN 33 and for dentin, the hardness has been reported in the range of 52 to 64 KHN or 46 to 53 VHN. 33 Loading time differences (10, 20, and 30 seconds) were not significant for either enamel or dentin evaluated at the same test load, this implies that a 10-second indentation duration is adequate to create a lasting indentation on the tooth surface.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in this investigation, the longer diagonal of the Knoop was compensated by the difficulty in determining where the tapered tip finishes on the surface of the dentin. 31 Without taking into account changes in indentation loads and time, the results obtained in this investigation for the KHN and VHN values of enamel and dentin are consistent with previously reported values: for example, the hardness of enamel has been reported in the range of 314 to 361 KHN 32 or 322 to 353 VHN 33 and for dentin, the hardness has been reported in the range of 52 to 64 KHN or 46 to 53 VHN. 33 Loading time differences (10, 20, and 30 seconds) were not significant for either enamel or dentin evaluated at the same test load, this implies that a 10-second indentation duration is adequate to create a lasting indentation on the tooth surface.…”
Section: Discussionsupporting
confidence: 91%
“…33 Loading time differences (10, 20, and 30 seconds) were not significant for either enamel or dentin evaluated at the same test load, this implies that a 10-second indentation duration is adequate to create a lasting indentation on the tooth surface. 33 Thus in our study we have measured the microhardness in Knoop hardness number.…”
Section: Discussionmentioning
confidence: 87%
“…25,28 The duration of caries removal with polymer burs was reported as 147.5 and 208.4 seconds in previous in vitro studies. 29,30 Unlike in Divya et al 2 , the statistically significant difference in the duration of the two methods may be due to the 120-second waiting time of the CMCR agent we used. That the CMCR agent caries removal time was found to be 300 seconds in another study using the same product supports this idea.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning the time required for complete caries removal, a digital stopwatch was used in this study as it represents simplicity, accuracy, and precision (10,21) . This study found that using a smart polymer bur for caries removal took longer than using a conventional carbide bur.…”
Section: Discussionmentioning
confidence: 99%